2008
DOI: 10.1136/sti.2007.029363
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to human papillomavirus vaccination among Chinese adolescent girls in Hong Kong: a qualitative-quantitative study

Abstract: Participants favoured HPV vaccination despite not feeling an immediate need to be vaccinated. Interventions could focus on providing professional information on HPV vaccination and raising adolescents' perceived need to take preventive measures against HPV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 12 publications
9
104
1
7
Order By: Relevance
“…Barriers to Pap tests include anxiety, embarrassment, and pain (Al-Naggar et al, 2010). Barriers to HPV vaccination include the high cost of the vaccine, anxiety about the vaccine's side effects, and pain (Kwan et al, 2008;Waller et al, 2009). Participants in this study identified the cost of HPV vaccine as a major barrier to intention to accept HPV vaccines.…”
Section: Discussionmentioning
confidence: 95%
“…Barriers to Pap tests include anxiety, embarrassment, and pain (Al-Naggar et al, 2010). Barriers to HPV vaccination include the high cost of the vaccine, anxiety about the vaccine's side effects, and pain (Kwan et al, 2008;Waller et al, 2009). Participants in this study identified the cost of HPV vaccine as a major barrier to intention to accept HPV vaccines.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies of Chinese women found misconceptions and knowledge deficits to be common regarding cervical cancer, HPV infection and HPV vaccination (Chan et al, 2007;Lee et al, 2007;Kwan et al, 2008;Li et al, 2012;Zhao et al, 2012;Choi et al, 2013). Most studies indicate a positive relationship between individuals' cancer-related risk perceptions and their attitudes, intentions, and actions regarding health protective and cancer preventive behaviors: if people consider cancer as controllable/preventable by their efforts they are more likely to seek medical care promptly, undergo cancer screening tests, or adopt healthy behaviors (Figueiras and Alves, 2007;Cameron, 2008;Sullivan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…3 These include the fear of needles (needle phobia) and fear of experiencing pain. 3,5 Fear of the pain of injection has been shown to be a factor associated with the acceptability of vaccines for both adults and children 2,3 and distress with injections has been found to be positively correlated with a recent bad experience with a needle or reaction at the injection site. 5 Parents have articulated their desire for limiting vaccine injections due to the pain and distress of the procedure and the sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] While many fears about vaccines are clearly rooted in myth, 4 others appear to be based on personal experiences and the experiences of others. 3 These include the fear of needles (needle phobia) and fear of experiencing pain.…”
Section: Introductionmentioning
confidence: 99%